PENERAPAN AZAS PENGELOLAAN DANA DESA TAHUN 2016 BERDASARKAN UU NOMOR 6 TAHUN 2014 TENTANG DESA DI DESA KALIREJO KECAMATAN WIROSARI KABUPATEN GROBOGAN - Kurniawati, Apita Isri; ., Kushandajani; ., Sulistyowati (Journal of Politic and Government Studies, 2018)
This research is purpose to know the application of village fund management principles on 2016 based on Constitution number 6 year 2014 about village with the case study Kalirejo Village, district Wirosari, Grobogan Regency year 2016.In this Research, the method that used is qualitative descriptive and taken at kalirejo village, district Wirosari, Grobogan Regency. The subjects of this research are the officials in Village Governm that have duty in directly planning, implementation, and controlling the village fund management. Data was taken by the interviewing the subjects, observation and documentation the process of data taking.The results of this research show that (1) Village Fund Management at Kalirejo in 2016 was going well and by the rules. (2) With the village fund, village government and citizens feel the development of their village which can be useful for them. (3) village Government and the related parties in this management of village fund have worked their duty based on the rules.Keyword : village fund management, constitution number 6 year 2014 about village, allocation of village fund